Reduction of Cr(VI) in Aqueous Solutions by Natural and Roasted Pyrite - DOLAK, IBRAHIM; TEGIN, IBRAHIM; GUZEL, REMZIYE; ZIYADANOGULLARI, RECEP (Asian Journal of Chemistry, 2010)
In present study, the effects of parameters such as acid concentration of the medium, amount of pyrite, initial Cr(VI concentration, contact time, temperature and particle size of pyrite on the reduction of Cr(VI) by discontinuous experiments using raw pyrite and the pyrite samples roasted at high temperatures in vacuum were examined. Considering that the pyrite sample converted FeS structure which has much higher reduction ability and is more homogeneous by roasting at high temperatures in vacuum, it was determined that using the pyrite sample in this way for the Cr(VI) reduction was much more efficient.